Handbook for critical cleaning : applications, processes, and controls - Kanegsberg, Barbara; Kanegsberg, Edward (Boca Raton, FL : CRC Press, 2011)
'Updated, re-organized, and rewritten, this second edition of a bestseller covers cleaning processes, applications, management, safety, and environmental concerns. A two-volume set, it discusses cleaning process applications, management, and safety and environmental concerns. International contributors give the text a global viewpoint. Color illustrations, video clips, and animations that make the information accessible are available from the website. The handbook is available for purchase individually or as the two-volume set'--
'Nearly all companies which manufacture or fabricate high-value physical objects (components, parts, assemblies) perform critical cleaning at one or more stages. These range from the giants of the semiconductor, aerospace, and biomedical world to a host of small to medium to large companies producing a dizzying array of components'--
[1] Cleaning agents and systems-- [2] Applications, processes, and controls
Includes bibliographical references and index.
Keywords: Metal cleaning; Cleaning compounds; Manufacturing processes; Surface preparation; Surface chemistry